PROFESSIONAL DEVELOPMENT OF TEACHERS OF NATURAL AND MATHEMATICAL EDUCATION AND TECHNOLOGIES IN THE DIGITAL EDUCATIONAL ENVIRONMENT - Naumova, Viktoriia (Neperervna profesìjna osvìta: teorìâ ì praktika, 2024)
The article is devoted to the consideration of the problem of teachers’ professional development in the fields of natural, mathematics, technology, and informatics. The purpose of the article is to substantiate the information and educational environment as a condition for the professional development of teachers of science and mathematics education and technology in Ukraine. Research methods: theoretical (analysis, synthesis, systematization; generalization, comparison); empirical (observation, online questionnaires); methods of mathematical statistics. Special attention is paid to the results of the online survey of teachers on the topic «The using of information and educational environment». 64 teachers took part in the survey. It was established that teachers consider «quality of content» and «availability of resources» to be the factors affecting the effectiveness of the information and educational environment of postgraduate pedagogical education. The main functions of the informational and educational environment of postgraduate education for teachers include providing access to relevant educational and methodological resources, creating distance learning programs, and providing examples of lessons and master classes. It was found that the content of the informational and educational environment reflects the ideas of people-centeredness, ensures the realization of the paradigm of equal access to quality education, and is based on the principles of accessibility, openness and continuity of education. It has been established that the effective integration of methodological concepts into the informational and educational environment of postgraduate pedagogical education significantly contributes to the professional growth and success of teachers.